Acid rain : papers presented at the fifteenth Consultative Council Meeting of the Watt Committee on Energy, London, 1 December 1983.: papers presented at the fifteenth Consultative Council Meeting of the Watt Committee on Energy, London, 1 December 1983. (2014) - Unknown
No abstract available